New Alpiniamides From Streptomyces sp. IB2014/011-12 Assembled by an Unusual Hybrid Non-ribosomal Peptide Synthetase Trans-AT Polyketide Synthase Enzyme - Paulus, Constanze; Rebets, Yuriy; Zapp, Josef; Rückert, Christian; Kalinowski, Jörn; Luzhetskyy, Andriy (Frontiers in Microbiology, 2018)
The environment of Lake Baikal is a well-known source of microbial diversity. The strain Streptomyces sp. IB2014/011-12, isolated from samples collected at Lake Baikal, was found to exhibit potent activity against Gram-positive bacteria. Here, we report isolation and characterization of linear polyketide alpiniamide A (1) and its new derivatives B-D (2-5). The structures of alpiniamides A-D were established and their relative configuration was determined by combination of partial Murata’s method and ROESY experiment. The absolute configuration of alpiniamide A was established through Mosher’s method. The gene cluster, responsible for the biosynthesis of alpiniamides (alp) has been identified by genome mining and gene deletion experiments. The successful expression of the cloned alp gene cluster in a heterologous host supports these findings. Analysis of the architecture of the alp gene cluster and the feeding of labeled precursors elucidated the alpiniamide biosynthetic pathway. The biosynthesis of alpiniamides is an example of a rather simple polyketide assembly line generating unusual chemical diversity through the combination of domain/module skipping and double bond migration events.